2018
DOI: 10.1038/s41598-018-34286-x
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the distribution of skin lipids and topically applied compounds in human skin using mass spectrometry

Abstract: The barrier functions of skin against water loss, microbial invasion and penetration of xenobiotics rely, in part, on the spatial distribution of the biomolecular constituents in the skin structure, particularly its horny layer (stratum corneum). However, all skin layers are important to describe normal and dysfunctional skin conditions, and to develop adapted therapies or skin care products. In this work, time-of-flight secondary ion mass spectrometry (ToF-SIMS) combined with scanning electron microscopy (SEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 49 publications
1
50
1
Order By: Relevance
“…Superior spatial resolution can be achieved using secondary ion mass spectrometry (SIMS) with spot sizes of 2 to 3 μm for the imaging of the [M-H 2 O+H] + ion of cholesterol (73). SIMS is often linked with time-of-flight (TOF) analyzers and using TOF-SIMS, both cholesterol and cholesterol sulfate have been imaged in skin at a resolution of a few micrometers (74,75). Even higher resolution (<0.1 μm) has been achieved with NanoSIMS to map 18 O isotope-labeled cholesterol in cells by monitoring the 18 O fragment ion (76).…”
Section: Discussionmentioning
confidence: 99%
“…Superior spatial resolution can be achieved using secondary ion mass spectrometry (SIMS) with spot sizes of 2 to 3 μm for the imaging of the [M-H 2 O+H] + ion of cholesterol (73). SIMS is often linked with time-of-flight (TOF) analyzers and using TOF-SIMS, both cholesterol and cholesterol sulfate have been imaged in skin at a resolution of a few micrometers (74,75). Even higher resolution (<0.1 μm) has been achieved with NanoSIMS to map 18 O isotope-labeled cholesterol in cells by monitoring the 18 O fragment ion (76).…”
Section: Discussionmentioning
confidence: 99%
“…These age‐related changes may occur either through intrinsic (degenerative process the body undergoes over time) or extrinsic (exposure to environmental factors) pathways. Currently, the existing literature regarding age‐related changes in skin lipid composition is not well documented, and different groups have reported variable effects on the concentrations of the three major lipid classes (ceramides, cholesterol, and fatty acids) found in skin (Boireau‐Adamezyk, Baillet‐Guffroy, & Stamatas, ; Rogers, Harding, Mayo, Banks, & Rawlings, ; Sjovall et al, ; Starr et al, ). In any case, it has been demonstrated that the age of the donor animal does not affect the performance of the grafts (Gore & De, ; Tognetti et al, ), and for this reason, there are practically no eligibility restrictions regarding the age of the donor (NHS UK).…”
Section: Discussionmentioning
confidence: 99%
“…CFAs are esterified fatty acids that are normally present in the synovial membrane phospholipids, and are characterized by a rapid absorption following topical administration. CFAs can easily permeate the skin owing to a passive and simple chemical-physical gradient favored by the lipidic nature of cell membranes ( Sjovall et al., 2018 ). Therefore, CFAs can be adsorbed at joint level and reach the synovial membrane, and can help to reduce joint pain, leading to an improvement in joint mobility.…”
Section: Discussionmentioning
confidence: 99%